Relation between green spaces and bird community structure in an urban area in Southeast Brazil - de Toledo, Maria Cecília Barbosa; Donatelli, Reginaldo José [UNESP]; Batista, Getulio Teixeira (Springer Nature, 2012)
Increased urbanization typically leads to an increase in abundance of a few species and a reduction in bird species richness. Understanding the structure of biotic communities in urban areas will allow us to propose management techniques and to decrease conflicts between wild species and human beings. The objective of this study was to describe the structure of the bird community in an urban ecosystem. The study was carried out in the city of Taubaté in southeastern Brazil. Point-counts were established in areas with different levels of tree density ranging from urban green spaces to predominantly built-up areas. We looked for a correlation between the richness/abundance of birds and the size of the area surveyed, the number of houses, the number of tree species and the number of individual trees. The results of multiple regression showed that bird richness had a direct relationship with vegetation complexity. The abundance and diversity of tree species were better predictors of bird species than the number of houses and size of the area surveyed. We discuss implications of this study for conservation and management of bird diversity in urban areas, such as the need to increase green areas containing a large diversity of native plant species. © 2011 Springer Science+Business Media, LLC.
Keywords: Bird-habitat relationship; Brazil; Urban birds; Urban vegetation; Aves